Effects of substituents and phosphine auxiliaries on the structures of Cu(I) clusters with functionalized 2, 2′-bipyridyl tetrazole ligands. (7th July 2016) - Chen, Jing-Lin; Xiao, Yi-Liang; Xia, Yong; Qiu, Lu; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui
Graphical abstract: Six new Cu(I) clusters with functionalized 2, 2′-bipyridyl tetrazole ligands respectively display tri-, di- and tetranuclear structures with diverse coordination geometries, which can be regulated by the methylation, NH-alkylation and phosphine alteration. Abstract: Six new Cu(I) clusters have been synthesized via the successive reaction of [Cu(MeCN)4 ](ClO4 ) with phosphine ancillary and functionalized 2, 2′-bipyridyl tetrazole. It is revealed that these Cu(I) cluster complexes respectively display tri-, di- and tetranuclear Cu(I) structures with diverse coordination geometries and various tridentate and tetradentate coordination modes induced by distinct ligand modifications and phosphine auxiliaries. It is demonstrated that the methylation of the 2, 2′-bipyridyl ring, the alkylation of the tetrazolyl-NH and the alteration of phosphine ancillary markedly influence the coordination environments of the Cu(I) atoms and the binding modes of the 2, 2′-bipyridyl tetrazole ligands, whereas the variation of the alkyl groups on the tetrazolyl ring has no obvious effects on the coordination manners of the resultant 2, 2′-bipyridyl tetrazole chelates and the structures of the resulting Cu(I) clusters.